The criminal code - Flavin, Martin 1883-1967 (powerhousefilms, 2021)
"Die Geschichte eines unbeholfenen jungen Mannes, der in vermeintlicher Notwehr einen Menschen tödlich verletzt hat und dafür zu zehn Jahren Zuchthaus verurteilt wird: Im Ordnungssystem des Strafvollzugs erlebt er das Gesetz der Häftlinge, das zu bedingungsloser Solidarität verpflichtet. Der von dem damals 34jährigen Howard Hawks inszenierte Gefängnisfilm gehört mit seinem humanitären Engagement und der Kunst seiner Darstellung zu den bedeutendsten des Genres."
Original: USA 1930
Special Features: Original mono audio ; Audio commentary with film historian Nora Fiore (2021) ; Behind the Mask (2021, 26 mins): author and critic Kim Newman discusses the non-horror career of actor Boris Karloff ; Codes and Convictions (2021, 30 mins): video essay by Jonathan Bygraves on the many adaptions of Marvin Flavin's The Criminal Code ; The Howard Hawks Masterclass with John Carpenter (1997, 36 mins): archival audio recording of a presentation by the cult filmmaker from the British Film Institute’s 1997 Howard Hawks retrospective at the National Film Theatre, London ; Lux Radio Theatre: ‘The Criminal Code’ (1939, 59 mins): radio adaptation starring Edward G Robinson, Beverly Roberts and Paul Guilfoyle ; Image galleries: on-set and promotional photography from The Criminal Code and its lost Spanish-language version, El código penal ; New and improved English subtitles for the deaf and hard-of-hearing ; Limited edition exclusive 36-page booklet with a new essay by Philip Kemp, Howard Hawks on The Criminal Code, an archival article on Hawks by Henri Langlois, an overview of contemporary critical responses, and film credits ; World premiere on Blu-ray ; Limited edition of 3,000 copies
Bildformat 1.37:1
Keywords: Film; Blu-Ray-Disc